Characterization of A Diesel Engine Operating with A Small Proportion of Methanol as a Fuel Additive in Biodiesel Blend - Mohd Hafizil, Mat Yasin; Talal, Yusaf; R., Mamat; Ahmad Fitri, Yusop (Elsevier, 2014)
Biodiesel has been a lucrative commodity in the current global economic trade as there is mounting concern for issues relating to the environment and oil depletion. Biodiesel has been proven to be the next alternative renewable fuel as it is environmentally friendly, sustainable and possesses similar combustion characteristics to petroleum diesel. However, due to the higher density and viscosity of biodiesel, pure biodiesel is not widely used in diesel engines. Therefore, the purpose of alcohol as a fuel additive is to improve the viscosity and density in the biodiesel blend. The focus of this study is to evaluate the performance and emissions of a small proportion of methanol (5% by volume) in a B20 blend and mineral diesel separately. A compression ignition (CI) Mitsubishi 4D68 multi-cylinder DI diesel engine was used in this work. Engine performance, combustion and exhaust emission characteristics were evaluated at two specific conditions. The first condition was an increase in engine speed from 1500 rpm to 3500 rpm at partial engine load and the second condition involved maintaining a constant speed of 2500 rpm at three different engine loads (0.05 MPa, 0.4 MPa and 0.7 MPa). Lower brake power was noticed when operating with B20 and B20 M5 blend. However, an increase in brake specific fuel consumption (BSFC) of 4–6% was observed when the engine was fueled with B20 and B20 M5. The results indicate that NOx emissions increase (up to 13%) while lower carbon monoxide (CO) and Carbon dioxide (CO2) (up to 17–18%) are observed in contrast with the mineral diesel.